HPLC‐UV and LC–MS Analyses of Acylquinic Acids in Geigeria alata (DC) Oliv. & Hiern. and their Contribution to Antioxidant and Antimicrobial Capacity. Issue 3 (1st December 2016) - Zheleva‐Dimitrova, Dimitrina; Gevrenova, Reneta; Zaharieva, Maya M.; Najdenski, Hristo; Ruseva, Silviya; Lozanov, Valentin; Balabanova, Vessela; Yagi, Sakina; Momekov, Georgi; Mitev, Vanio
Abstract: Introduction: Geigeria alata is a traditional plant used in Sudanese folk medicine for treatment of diabetes, cough, epilepsy and intestinal complaints. Objective: To analyze phenolic acids in Geigeria alata roots and leaves and to evaluate their antioxidant and antimicrobial activities. Methodology: Phenolic acids in the aqueous‐methanol extracts were identified by LC–MS. Major compounds were isolated using low‐pressure liquid chromatography. The quantitative analysis of phenolic acids was performed by a validated HPLC‐UV method with limits of detection ranging from 0.04 to 0.57 μg/mL. 2, 2‐Diphenyl‐1‐picrylhydrazyl (DPPH), 2, 2′‐azinobis‐(3‐ethylbenzothiazine‐6‐sulphonic acid) (ABTS) and ferric reducing antioxidant power (FRAP) methods were used for antioxidant activity evaluation. In addition, the minimal inhibitory concentration and the minimal bactericidal concentration against a panel of pathogenic bacteria and fungi were determined by the broth microdilution test. Results: For the first time protocatechuic, caffeic, p‐ coumaroylquinic, caffeoylsinapoylquinic, caffeoylferuloylquinic, three feruloylquinic, six caffeoylquinic acids, and a caffeic acid hexoside were detected in Geigeria alata roots by LC–MS. HPLC‐UV analyses showed that 3, 5‐dicaffeoylquinic acid (25.96 ± 2.08 mg/g dry weight (DW)) was the most abundant phenolic acid in roots, while 4, 5‐dicaffeoylquinic acid (8.99 ± 0.56 mg/g DW) was the main compound present in leaves. 3, 5‐Dicaffeoylquinic acid demonstrated stronger radical scavenging activity and reducing power compared with the crude extracts and the positive control 5‐caffeoylquinic acid. 3, 4, 5‐Tricaffeoylquinic acid revealed the highest antibacterial potential against the penicillin sensitive and resistant Staphylococcus aureus strains, as well as methicillin‐resistant S. aureus . Conclusion: The caffeoylquinic acids content of up to 6.22% in Geigeria alata roots establishes this species as a new source rich in these bioactive molecules. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The aim of this study was to analyze phenolic acids of Geigeria alata roots and leaves by LC‐MS and HPLC‐UV, to isolate the main compounds using low‐bar liquid chromatography and to evaluate their antioxidant and antimicrobial activity. A variety of acylquinic acids were identified in G. alata roots and leaves. 3, 5‐dicaffeoylquinic acid was the most abundant acylquinic acid in roots and demonstrated strong antioxidant activity, while 3, 4, 5‐tricaffeoylquinic acid revealed the highest antibacterial potential.